Hot Line Work Resources Fulfillment Strategy Selection using SMART Methods - Setyawan, Irfan Agus; Putro, Utomo Sarjono (The Indonesian Journal of Business Administration, 2015)
Abstract. Electricity supply has become the main part of an industry process, even more in oil and gas industry. Operating a safe and reliable electric power system requires continues maintenance of all equipment from generation side until distribution side. Maintenance activities of transmission and distribution line could be performed either offline or online condition. Maintenance activities of transmission and distribution line that is conducted without shutting down the line or on energized line, it is called Hot Line Work. This maintenance method is needed to prevent production loss. Hot Line Work activities require specific and competence resource. In this study, we propose alternatives of Hot Line Work resources fulfillment strategy.In this study, Kepner-Tragoe Problem Analysis is applied to analyze the problem and Simple Multi Attribute Rating Technique (SMART) applied in decision making process. This method is utilized since SMART method allow complex problem to be decomposed into sets of simpler judgment. This simplicity influences directly on the understanding of the decision maker about the process used in the solution of the problem since the decision making process involving many decision makers from various background. Each steps of SMART method are combined with other tools to ease and facilitate the process. The TOWS matrix is used in alternative generation. Brainstorming tool is used in attribute identification. Interval scale form is used in measuring the weight of attribute and attribute value to each alternative. From the TOWS matrix, 4 alternatives are generated: hire new employee, use secondee contract, use service contract or use man-hours contract. Alternative 1 – hire new employee – place the highest position for cost needed and total benefit value. Alternative 2 – use secondee contract – place the second position in term of cost needed and total benefit value. The needed cost of Alternative 2 is one third than Alternative 1, but total benefit value is close to Alternative 1. Alternative 3 – use service contract – place the third position of total benefit value. Alternative 3 and Alternative 4 – use man-hours contract – has the same needed cost and it is slightly lower than Alternative 2, but the total benefit value is much lower than Alternative 2. 2 This study result the selected solution is Alternative 2 since it is intermediate choice. It cost Rp 2 Billion more than Alternative 3, but offers much higher benefits. By using Alternative 2, Electrical Department still could maintain safety, service quality, and salary and career path control of Hot Line Work resources, but the needed cost is moderate. From the sensitivity analysis, it is also robust that Alternative 2 is moderate choice.Keywords: Decision Analysis, Hot Line Work, Simple Multi Attribute Rating Technique, Resources Strategy